Calcium isotopic ecology of Turkana Basin hominins - Jeremy E. Martin (Nature Portfolio, 2020)
Non-traditional stable isotopes, such as of calcium, have potential to expand our understanding of ancient diets. Here, Martin et al. use stable calcium isotopes recovered from fossil tooth enamel to compare the dietary ecology of hominins and other primates in the Turkana Basin 2-4 million years ago.